2017
DOI: 10.1002/2017ja024079
|View full text |Cite
|
Sign up to set email alerts
|

Linear theory of the current sheet shear instability

Abstract: The present study investigates the linear properties of the current sheet shear instability (CSSI) based on the two‐fluid equations. The mode is typically excited in the thin current layer formed around the X line during a quasi‐steady phase of collisionless reconnection and is considered to give rise to the anomalous momentum transport. The linear analyses are carried out for a realistic current sheet as evolved in collisionless reconnection, where the current density profile is produced by the nonuniform ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Both analyses noted that the interaction between the reconnection and the instability was very complex and that the two behaviors were hard to separate. Another closely related instability is the current sheet shear instability proposed by Fujimoto and Sydora (, ). Following an initial study by Hesse et al (), which suggested that the LHDI induces a velocity shear by modifying the diamagnetic drift and density profile leading to the Kelvin‐Helmholtz instability, Lapenta and Brackbill () and Lapenta et al () carried out 3‐D simulations in a Harris sheet and found kink‐like modes that they believe resulted from the nonlinear evolution of the LHDI that led to a Kelvin‐Helmholtz‐like instability.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Both analyses noted that the interaction between the reconnection and the instability was very complex and that the two behaviors were hard to separate. Another closely related instability is the current sheet shear instability proposed by Fujimoto and Sydora (, ). Following an initial study by Hesse et al (), which suggested that the LHDI induces a velocity shear by modifying the diamagnetic drift and density profile leading to the Kelvin‐Helmholtz instability, Lapenta and Brackbill () and Lapenta et al () carried out 3‐D simulations in a Harris sheet and found kink‐like modes that they believe resulted from the nonlinear evolution of the LHDI that led to a Kelvin‐Helmholtz‐like instability.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The signatures in the simulations are complicated by wave‐like structures. A number of simulation studies in 2‐D and 3‐D have reported wave‐like phenomena (Divin et al, ; Fujimoto & Sydora, , ; Hesse et al, ; Karimabadi et al, ; Lapenta et al, ; Lapenta & Brackbill, ; Shinohara et al, ; Yin et al, ). For instance, in an electron positron plasma, Yin et al () found patchy reconnection and a very complex interaction between the tearing mode and kink mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The free energy source for the instability are inhomogeneities in the magnetic field and plasma pressure which drive the relative drifts of electrons and ions. Even though the LHDI does not significantly alter the reconnection rate it does lead to enhanced anomalous plasma transport which relaxes gradients, for instance the density, which in turn can give rise to secondary instabilities such as the CSSI that is driven by the electron flow shear (Fujimoto & Sydora 2017). The electromagnetic branch of the LHDI causes kinking of the current sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, reconnection in Earth's magnetosphere is not necessarily a quasi‐2‐D process since observations show remarkable disagreements with the classical 2‐D reconnection model (Runov et al, ). The addition of variations in the third direction (out of plane) allows the growth of instabilities with wave vectors along the X line, such as the lower hybrid drift instability, oblique tearing instability, and current sheet shear instability (Daughton, ; Daughton et al, ; Fujimoto & Sydora, ). These waves/instabilities may play important roles in regulating the dissipation process in reconnection (Ji et al, ).…”
Section: Introductionmentioning
confidence: 99%